To What Extent Are Analysts' Reports Useful? - Ebinesan, Noel Artputhan (2006)
This dissertation evaluates the topic question as above using three methods. Specifically it focuses on the forecasts produced by analysts. The first method uses the literature review methodology to answer the research question based on research conducted by others. The second method extends the empirical literature to the East Asian economies of Thailand, Malaysia and Singapore and as well includes Hong Kong. The aim here is to see if analyst forecasts are being incorporated into share price and hence proofs its level of usefulness in each stock market. Finally third method looks at analyst reports directly to evaluate the research question based on the case study methodology. Overall, based on the limited time available and scope of the dissertation, analyst forecast are useful depending on certain factors and hence this report is useful as well depending on certain factors like the level of efficiency observed in stock market.